Spectacle-Wear Compliance in School Children in Concepción Chile. (December 2014) - Barria von-Bischhoffshausen, Fernando; Muñoz, Beatriz; Riquelme, Ana; Ormeño, Maria Jose; Silva, Juan Carlos
Abstract Purpose: Although international policies promote programs for correction of refractive errors in school children, recent studies report low compliance with respect to spectacle wear. Our aim was to assess spectacle-wear compliance and identify associated visual factors among children participating in Chile's school spectacle provision program. Methods: A total of 270 school children were prescribed spectacles and monitored after 1 year. Visual acuity, refractive error, reasons for not wearing spectacles, and self-reported visual function were assessed. Compliance is reported as the proportion of children wearing spectacles at the 1-year visit. Factors associated with compliance and reasons for not wearing spectacles were examined using contingency table analyses. Logistic models were constructed to assess independently associated factors. Results: Only 204 children (76%) participated in the 1-year follow-up. Mean age was 10 years (range 4–19 years); 58% were girls, 42% boys. Overall compliance was 58%. Spectacle use was independently associated with age and refractive error. Older children were less likely to be compliant (odds ratio, OR, 0.8, 95% confidence interval, CI, 0.76–0.92/year of increasing age). Compared with children with refractions of −0.75 to +0.75 diopters, both myopic and hyperopic children were more compliant (OR 4.93, 95% CI 2.28–10.67 and OR 2.37, 95% CI 1.06–5.31, respectively). Primary reasons for not wearing spectacles included breakage/loss in younger children, and disliking the appearance in teenagers. Conclusion: We found greater compliance in spectacle wear than that reported in most published studies. Guidelines for provision of children's spectacles should consider excluding children with mild refractive error and improving spectacle quality and appearance.